Analysis of the Presentation of Financial Statements of a Non-Profit Organization (Case Study of Independent Private Foundation Orphanage Bengkulu City) - Neri Susanti; Rinto Noviantoro; Anggini Anggini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The characteristics of non-profit organizations are different from business organizations. The fundamental difference lies in the way the organization obtains the resources needed to carry out its various operating activities. non-profit organizations obtain resources from donations from other contributing members who do not expect anything in return from the organization while business organizations obtain resources from the capital of owners or investors who expect a return on any profits earned by the organization.This study aims to analyze the presentation of financial statements of non-profit organizations (a case study of the Bengkulu city independent private foundation orphanage). The purpose of this study was to determine the suitability of the application of ISAK 35 concerning financial statements of non-profit organizations in achieving transparency and accountability at the orphanage of the private foundation mandiri Bengkulu city. The data analysis used is descriptive comparative, which is a research method that compares a theory that applies to events that occur in the field.The results of this study indicate that the Bengkulu city independent private foundation orphanage in general has not made financial reports in accordance with ISAK 35, but in the financial statements made by the independent private foundation orphanage has implemented ISAK 35 even though it is only 55.55%, while for transparency and accountability as a whole the orphanage has been transparent and accountable, in its financial statements.